Do Environmental, Social, and Governance (ESG) Factors Affect Firm Value in Indonesia’s Environmentally Sensitive Industries? - Nisa Iksi Rosa; Ana Noveria (Jurnal Manajemen Bisnis, 2025)
This study aims to analyze the influence of Environmental, Social, and Governance (ESG) performance on company value proxied by the Price to Earnings Ratio (PER), especially in industries that are sensitive to environmental issues in Indonesia. Using five years of panel data and panel regression, the study evaluated the impact of each ESG pillar separately or in combination on company value. The results of the study show that the overall ESG score has a positive and significant effect on PER. Among the three pillars, the Social aspect (SOC) had the strongest and most significant influence, followed by the positive but insignificant Environmental aspect (ENV), while the Governance aspect (GOV) showed no significant influence. These findings indicate that investors in environmentally sensitive sectors respond most strongly to social and environmental performance as they are perceived to reflect risk management and long-term operational sustainability. This research refers to three main theories: Stakeholder Theory which emphasizes the importance of social and environmental engagement; Shareholder Theory that sees ESG as a signal of company quality; and Legitimacy Theory which highlights ESG as a tool to gain social legitimacy. The practical implications of these findings are the importance of companies strengthening their commitment to social and environmental pillars strategically, investors to consider ESG aspects in decision-making, and regulators to improve the standards and credibility of ESG disclosures in Indonesia